A Systematic Literature Review of Investment Strategies in Perfect Capital Markets: Insights from the PRISMA Framework - Wijaya, Fanji; Waspada, Ikaputera; Sari, Maya (Research Synergy Foundation, 2024)
Investment strategies in capital markets play a crucial role in optimizing returns and managing risk. This article reviews recent literature using the PRISMA framework to identify and analyze effective investment strategy approaches in flawless capital markets. There are 6,411 Scopus Databases, 1,336 databases on specific and Reports assessed for eligibility (n = 263), and studies included in the review (n = 12). This study explores the integration of Environmental, Social, and Governance (ESG) and Socially Responsible Investment (SRI) strategies supported by data-driven quantitative models and cutting-edge technologies, such as machine learning and big data analytics. This research highlights the importance of cross-cultural and regional risk diversification strategies, as well as the implementation of advanced technologies, such as Backpropagation Neural Network (BPNN), in asset valuation and market prediction. Findings reveal that optimizing quantitative strategies with artificial intelligence enables more precise and responsive decision-making to market volatility, and data-driven approaches are particularly relevant in emerging economies to address liquidity risk and regulatory uncertainty. The reformulation of ownership and capital structure policies is proposed to encourage productive collaboration between foreign and domestic investors. In addition, innovation-based strategies, such as the use of digital coins and textual analysis of opinions, offer competitive advantages in an evolving capital market. This research emphasizes the importance of synergies between technological innovation and strategic investment policies to maximize opportunities in a dynamic global market and ensure long-term sustainability.